Liquid composition comprising electrically conductive polymer particles and organic solvent forming azeotrope with water

By adding organic solvents with a specific boiling point range to the aqueous PEDOT/PSS dispersion to form an azeotrope, the problems of fast drying speed of the dispersion and reduced thin-layer resistance are solved, and the effect of preparing a high-thin resistance conductive layer is achieved.

CN119529583APending Publication Date: 2025-02-28HERAEUS EPURIO GMBH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411774422.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-06-28
Filing Date
2019-06-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing aqueous PEDOT/PSS dispersions dry quickly when exposed to air, causing the device to be blocked. The addition of high boiling solvents slows down the drying rate, but the thin layer resistance of the conductive polymer film will significantly reduce, affecting its performance in some industrial uses.

Method used

A liquid composition is provided, comprising composite particles of polythiophene and polyanion, the liquid phase consisting of water and an organic solvent having a specific boiling point range, the liquid phase is an azeotrope or capable of forming an azeotrope to form a conductive layer with a sufficiently high thin layer resistance.

Benefits of technology

The liquid composition can slow down the drying speed without increasing the resistance of the conductive polymer film thin layer, avoid device clogging, and meet the requirements for preparing antistatic coatings, electromagnetic radiation shielding, or hole transport layers in organic electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171057600000061
    Figure BDA0005171057600000061
  • Figure BDA0005171057600000131
    Figure BDA0005171057600000131
  • Figure BDA0005171057600000132
    Figure BDA0005171057600000132
Patent Text Reader

Abstract

The present application relates to a liquid composition comprising conductive polymer particles and an organic solvent forming an azeotrope with water. The present invention relates to a liquid composition comprising i) particles comprising a complex of a polythiophene and a polyanion; ii) a liquid phase wherein the liquid phase comprises iia) water and iib) at least one organic solvent having-a boiling point in the range of 110 to 250 DEG C, determined at a 1013 mbar pressure, and-a solubility in water, determined at 25 DEG C, of at least 10 wt% wherein the liquid phase is an azeotrope or is capable of forming an azeotrope. The invention also relates to a method for producing a layered body, to a layered body obtainable by such a method and to the use of a liquid composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of June 26, 2019, application number 201980048725.9, and invention name “Liquid composition comprising conductive polymer particles and an organic solvent that forms an azeotrope with water”. Technical Field

[0002] The present invention relates to a liquid composition comprising particles comprising a composite of polythiophene and a polyanion, a method for preparing a layered body, a layered body obtainable by such a method and the use of the liquid composition. Background Art

[0003] Conductive polymers are of increasing economic importance, since polymers have advantages over metals in terms of processability, weight and the ability to adjust properties in a targeted manner by chemical modification. Examples of known π-conjugated polymers are polypyrroles, polythiophenes, polyanilines, polyacetylenes, polyphenylenes and poly(p-phenylene-vinylene). Layers formed from conductive polymers are used for different industrial purposes, for example as polymer counter electrodes in capacitors or for through-plating of electronic circuit boards. Conductive polymers are prepared chemically or electrochemically by oxidation from monomer precursors, such as optionally substituted thiophenes, pyrroles and anilines and certain optionally oligomeric derivatives thereof. In particular, chemical oxidative polymerization is widely used, since the process is easy to implement industrially in liquid media or on different substrates.

[0004] A particularly important polythiophene used industrially is poly(3,4-ethylenedioxythiophene) (PEDOT or PEDT), which is described, for example, in EP 0 339 340 A2 and is prepared by chemical polymerization of 3,4-ethylenedioxythiophene (EDOT or EDT) and which in its oxidized form has a very high conductivity. A. Elschner, S. Kirchmeyer, W. Lowenich, W. ), U. Merker, K. Reuter, "PEDOT Principles and Applications of an Intrinsically Conductive Polymer", CRC Press, 2011, provides an overview of various poly(3,4-alkylenedioxythiophene) derivatives, in particular poly(3,4-ethylenedioxythiophene) derivatives and their monomer units, synthesis and uses. Typically, 3,4-ethylenedioxythiophene is polymerized in water in the presence of a polyanion such as polystyrenesulfonate (PSS), thereby obtaining an aqueous composition containing a complex of a cationic polythiophene with a polyanion (commonly referred to as "PEDOT / PSS"). Such a process is disclosed, for example, in EP 0 440 957 A2. Due to the polyelectrolyte properties of PEDOT as a polycation and PSS as a polyanion, these compositions are not true solutions but dispersions. The extent to which a polymer or a portion of said polymer is soluble or dispersed in this environment depends on the weight ratio of polycation to polyanion, the charge density of the polymer, the salt concentration of said environment and the nature of the surrounding medium (V. Kabanov, Russian Chemical Reviews 74, 2005, 3-20).

[0005] PEDOT / PSS dispersions are of particular industrial interest. Transparent conductive films have a variety of uses, for example as antistatic coatings or as conductive layers in electronic components, for example as hole injection layers in organic light emitting diodes (OLEDs), in organic photovoltaic elements (OPV elements) or in organic photodetectors (OPDs) as intermediate layers, or as electromagnetic interference (EMI) shielding materials. The conductive films are also commonly used to form conductive polymer layers, in particular solid electrolyte layers or polymer outer layers, in the manufacture of solid electrolyte capacitors.

[0006] However, aqueous PEDOT / PSS dispersions known from the prior art usually dry very quickly when exposed to air, resulting in clogging of devices used to apply these dispersions to substrates, such as slot coaters, inkjet printers or spray nozzles. In order to reduce the drying speed of aqueous PEDOT / PSS dispersions, high boiling point solvents such as ethylene glycol and DMSO (i.e. solvents with a boiling point higher than that of water) have been added. Such methods are disclosed, for example, in EP 0 686 662 A2. However, the addition of such high boiling point solvents also significantly reduces the sheet resistance of the resulting conductive polymer film, which is undesirable when using the conductive polymer layer as an antistatic coating, as an electromagnetic radiation shield or in an organic light emitting diode (OLED) or in an organic photovoltaic (OPV) element or in an organic photodetector (OPD) as a hole transport layer. Summary of the invention

[0007] The present invention is based on the object of overcoming the disadvantages arising from the prior art in connection with liquid compositions comprising polythiophenes, in particular with PEDOT / PSS dispersions.

[0008] Specifically, the present invention is based on the object of providing a liquid composition comprising polythiophene, which can be used to form a conductive layer having a sufficiently high sheet resistance, thereby allowing the use of the composition to form an antistatic coating or an electromagnetic radiation shield or for the preparation of a hole transport layer in an organic light emitting diode (OLED) or in an organic photovoltaic (OPV) element or in an organic photodetector (OPD), wherein the liquid composition does not lead to clogging of the devices used to apply the dispersion to a substrate, such as an inkjet printer or a spray nozzle.

[0009] |1| A liquid composition comprising:

[0010] i) particles comprising a composite of polythiophene and a polyanion;

[0011] ii) a liquid phase, wherein the liquid phase comprises

[0012] iia) water, and

[0013] iib) at least one organic solvent having

[0014] a boiling point in the range of 110 to 250° C., preferably in the range of 120 to 225° C. and most preferably in the range of 130 to 200° C., measured at a pressure of 1013 mbar, and

[0015] - a solubility in water measured at 25°C of at least 10 wt%, preferably at least 25 wt%, more preferably at least 50 wt% and most preferably at least 90 wt%;

[0016] wherein the liquid phase is an azeotrope or is capable of forming an azeotrope.

[0017] |2| The liquid composition according to embodiment |1|, wherein the liquid composition is a dispersion, wherein particles i) are dispersed in the liquid phase ii).

[0018] |3| The liquid composition according to embodiment |1| or |2|, wherein the polythiophene is poly(3,4-ethylenedioxythiophene) (PEDOT).

[0019] |4| The liquid composition according to any one of embodiments |1| to |3|, wherein the polyanion is an anion of polystyrene sulfonic acid (PSS).

[0020] |5| The liquid composition according to any one of embodiments |1| to |4|, wherein the complex of polythiophene and polyanion is a PEDOT / PSS complex.

[0021] |6| The liquid composition according to any one of embodiments |1| to |5|, wherein the weight average diameter (d 50 ) is in the range of 10 nm to 2,000 nm, more preferably in the range of 20 nm to 500 nm, and more preferably in the range of 25 nm to 50 nm.

[0022] |7| A liquid composition according to any one of embodiments |1| to |6|, wherein the organic solvent iib) is an alcohol, preferably ethylene glycol monoethyl ether, ethylene glycol monobutyl ether or diacetone alcohol; an ether, preferably diethylene glycol dimethyl ether (diethylene glycol dimethyl ether / Diglyme); or a mixture thereof.

[0023] |8| The liquid composition according to embodiment |7|, wherein the organic solvent iib) is an alcohol.

[0024] |9| The liquid composition according to embodiment |8|, wherein the alcohol is selected from the group consisting of ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diacetone alcohol or a mixture thereof.

[0025] |10| The liquid composition according to embodiment |9|, wherein the alcohol is diacetone alcohol.

[0026] |11| The liquid composition according to embodiment |9|, wherein the alcohol is ethylene glycol monoethyl ether.

[0027] |12| The liquid composition according to embodiment |9|, wherein the alcohol is ethylene glycol monobutyl ether.

[0028] |13| The liquid composition according to any one of embodiments |1| to |12|, wherein the liquid composition further comprises iii) at least one additive selected from the group consisting of UV stabilizers, surfactants, low boiling point solvents, pH adjusters, crosslinkers, rheology modifiers, or a combination of at least two of the additives.

[0029] |14| The liquid composition according to embodiment |13|, wherein the low boiling point solvent is ethanol.

[0030] |15| A liquid composition according to embodiment |13| or |14|, wherein the liquid composition comprises a low boiling point solvent, preferably ethanol, in an amount of 10 to 90 wt%, more preferably 20 to 85 wt% and most preferably 30 to 80 wt%, in each case based on the total weight of the liquid composition.

[0031] |16| The liquid composition according to any one of embodiments |13| to |15|, wherein the UV stabilizer is gallic acid, a derivative of gallic acid, or a mixture thereof.

[0032] |17| The liquid composition according to embodiment |16|, wherein the derivative of gallic acid is an ester of gallic acid and sugar.

[0033] |18| The liquid composition according to embodiment |17|, wherein the derivative of gallic acid is gallotannin.

[0034] |19| The liquid composition according to embodiment |18|, wherein the gallotannin is tannic acid.

[0035] |20| The liquid composition according to embodiment |16|, wherein the derivative of gallic acid is an alkyl ester, alkenyl ester, cycloalkyl ester, cycloalkenyl ester or aryl ester of gallic acid.

[0036] |21| The liquid composition according to embodiment |20|, wherein the ester has 1 to 15 C atoms, preferably 1 to 6 C atoms in the alkyl, alkenyl, cycloalkyl, cycloalkenyl or aryl group of the ester.

[0037] |22| The liquid composition according to embodiment |21|, wherein the ester is methyl gallate, ethyl gallate, propyl gallate or a mixture of at least two of these esters.

[0038] |23| The liquid composition according to any one of embodiments |13| to |22|, wherein the crosslinking agent is a tetraalkyl orthosilicate.

[0039] |24| A liquid composition according to embodiment |23|, wherein the tetraalkyl orthosilicate is selected from the group consisting of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, orthosilicates, at least partial hydrolysis products of these orthosilicates, and a mixture of at least two of these orthosilicates.

[0040] |25| The liquid composition according to embodiment |24|, wherein the tetraalkyl orthosilicate is tetraethyl orthosilicate (TEOS).

[0041] |26| A liquid composition according to any one of embodiments |1| to |25|, wherein the liquid composition comprises the complex i) of polythiophene and polyanion, preferably a PEDOT / PSS complex, in an amount of 0.001 to 2.5 wt%, more preferably 0.005 to 1.0 wt% and most preferably 0.01 to 0.5 wt%, in each case based on the total weight of the liquid composition.

[0042] |27| A liquid composition according to any one of embodiments |1| to |26|, wherein the liquid composition comprises water iia) in an amount in the range of 10 to 98 wt%, preferably in the range of 20 to 97 wt%, more preferably in the range of 30 to 96 wt% and even more preferably in the range of 40 to 95 wt%, in each case based on the total weight of the liquid composition.

[0043] |28| The liquid composition according to any one of embodiments |1| to |27|, wherein the liquid composition comprises the at least one organic solvent iib) in an amount of less than 10 wt%, preferably less than 8.5 wt% and more preferably less than 7 wt%, in each case based on the total weight of the liquid composition. In the case of two or more organic solvents iib), the amount defines the total amount of organic solvents iib).

[0044] |29| The liquid composition according to any one of embodiments |1| to |28|, wherein the dry layer prepared using the liquid composition has a surface area of ​​at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq and more preferably at least 1×10 7 Sheet resistance of Ω / sq.

[0045] |30| The liquid composition according to any one of embodiments |1| to |29|, wherein a dry layer prepared with the liquid composition has an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99% and most preferably at least 99.5%.

[0046] |31| The liquid composition according to any one of embodiments |1| to |30|, wherein a dried layer prepared with the liquid composition has a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H and most preferably at least 9H.

[0047] |32| A liquid composition according to any one of embodiments |1| to |31|, wherein the pH value of the liquid composition is not less than 2.5, more preferably the pH value is in the range of 2.5 to 6, even more preferably in the range of 2.5 to 5 and most preferably in the range of 2.5 to 4, wherein the pH value is measured at a temperature of 25°C.

[0048] |33| A method for preparing a layered body, comprising the following method steps:

[0049] A) providing a substrate;

[0050] B) applying a liquid composition according to any one of embodiments |1| to |32| to the substrate;

[0051] C) at least partially removing said liquid phase ii) from said liquid composition to obtain a layered body comprising a conductive layer applied onto said substrate.

[0052] |34| The method according to embodiment |33|, wherein the application of the liquid composition in method step B) is performed by slot coating, spraying or inkjet printing.

[0053] |35| A layered body obtainable by the method according to Example |34|.

[0054] |36| The layered body according to embodiment |35|, wherein the conductive layer of the layered body is characterized by at least one of the following properties (α1) to (α3), preferably all of these properties:

[0055] (α1) Sheet resistance is at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq and more preferably at least 1×10 7

[0056] Ω / sq;

[0057] (α2) The internal transmittance is at least 98%, preferably at least 98.5%, more preferably at least 99% and most preferably

[0058] At least 99.5%;

[0059] (α3) The pencil hardness is at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.

[0060] |37| Use of the liquid composition according to any one of embodiments |1| to |32| for producing an antistatic coating or electromagnetic radiation shielding or for preparing a hole transport layer in an organic light emitting diode (OLED) or in an organic photovoltaic (OPV) element or in an organic photodetector (OPD). DETAILED DESCRIPTION

[0061] The above objectives are facilitated by a liquid composition comprising:

[0062] i) particles comprising a composite of polythiophene and a polyanion;

[0063] ii) a liquid phase, wherein the liquid phase comprises

[0064] iia) water, and

[0065] iib) at least one organic solvent having

[0066] a boiling point in the range of 110 to 250° C., preferably in the range of 120 to 225° C. and most preferably in the range of 130 to 200° C., measured at a pressure of 1013 mbar,

[0067] and

[0068] - at least 10 wt%, preferably at least 25 wt%, more preferably at least 50 wt%, measured at 25°C

[0069] and most preferably at least 90 wt% solubility in water;

[0070] wherein the liquid phase is an azeotrope or is capable of forming an azeotrope.

[0071] According to a preferred embodiment of the liquid composition of the present invention, the liquid composition is a dispersion, wherein the particles i) are dispersed in the liquid phase ii).

[0072] In the sense of the present invention, a liquid phase "capable of forming an azeotrope" is a liquid phase which, when heated, reaches a temperature at which the composition becomes an azeotrope. Preferably, it is a liquid phase consisting of water and a high boiling point solvent which, when heated, reaches a temperature at which the composition becomes an azeotrope.

[0073] "A solubility in water measured at 25°C of at least 10 wt.-%" is obtained if, at a temperature of 25°C, at least 10 g of organic solvent iib) can be dissolved in 100 g of water iia).

[0074] It has been unexpectedly discovered that the undesirable increase in sheet resistance when using a high boiling point organic solvent that forms an azeotrope with water can be avoided by adding a high boiling point organic solvent to the aqueous PEDOT / PSS dispersion for the purpose of slowing down the drying rate of the aqueous dispersion.

[0075] The liquid composition according to the invention comprises particles comprising polythiophene and polyanion as component i). In this case, polythiophene having the following general formula is particularly preferred:

[0076]

[0077] in

[0078] A represents an optionally substituted C1-C5 alkylene group,

[0079] R represents a linear or branched optionally substituted C1-C 18 Alkyl, optionally substituted C5-C 12 Cycloalkyl, optionally substituted C6-C 14 Aryl, optionally substituted C7-C 18 Aralkyl, optionally substituted C1-C4-hydroxyalkyl or hydroxy, wherein 0 to 8 radicals R may be bonded to A and in the case of more than one radical, they may be identical or different.

[0080] The polythiophenes preferably carry H in each case at the terminal groups.

[0081] In the context of the present invention, C1-C5 alkylene A is preferably methylene, ethylene, n-propylene, n-butylene or n-pentylene. 18 The alkyl group R preferably represents a linear or branched C1-C 18 Alkyl, such as methyl, ethyl, n-propyl or isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl or n-octadecyl; C5-C 12 Cycloalkyl R represents, for example, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl or cyclodecyl; C5-C 14 Aryl R represents, for example, phenyl or naphthyl; and C7-C 18Aralkyl R represents, for example, benzyl, o-tolyl, m-tolyl, p-tolyl, 2,3-xylyl, 2,4-xylyl, 2,5-xylyl, 2,6-xylyl, 3,4-xylyl, 3,5-xylyl or mesityl. The preceding list serves to illustrate the invention and should not be considered conclusive.

[0082] In the context of the present invention, a large number of organic groups are possible as optional further substituents of the group A and / or the group R, for example alkyl groups, cycloalkyl groups, aryl groups, aralkyl groups, alkoxy groups, halogen groups, ether groups, thioether groups, disulfide groups, sulfoxide groups, sulfone groups, sulfonate groups, amino groups, aldehyde groups, keto groups, carboxylate groups, carboxylic acid groups, carbonate groups, carboxylate groups, cyano groups, alkylsilyl groups and alkoxysilyl groups and carboxamide groups.

[0083] Polythiophenes in which A represents an optionally substituted C2-C3 alkylene group are particularly preferred. Poly(3,4-ethylenedioxythiophene) is very particularly preferred as the polythiophene.

[0084] Polythiophene can be neutral or cationic. In a preferred embodiment, it is cationic, "cationic" only related to the charge on the polythiophene main chain. Depending on the substituents on the group R, polythiophene can carry positive and negative charges in the structural unit, the positive charge is located on the polythiophene main chain and the negative charge is optionally on the group R substituted with a sulfonate group or a carboxylate group. In this case, the positive charge of the polythiophene main chain can be partially or completely satisfied by anionic groups optionally present on the group R. In general, in these cases, polythiophene can be cationic, neutral or even anionic. Nevertheless, in the context of the present invention, it is considered a cationic polythiophene because the positive charge on the polythiophene main chain is the determining factor. The positive charge is not shown in the formula because its exact number and position cannot be absolutely determined. However, the number of positive charges is at least 1 and at most n, where n is the total number of all repeating units (same or different) in the polythiophene.

[0085] To compensate for the positive charge of the polythiophene, the particles comprising polythiophene i) additionally comprise polyanions, which are preferably based on polymers functionalized with acid groups. Anions of polymeric carboxylic acids, such as polyacrylic acid, polymethacrylic acid or polymaleic acid, or polymeric sulfonic acids, such as polystyrenesulfonic acid and polyvinylsulfonic acid, are particularly suitable as polyanions. These polycarboxylic acids and polysulfonic acids can also be copolymers of vinylcarboxylic acid and vinylsulfonic acid with other polymerizable monomers, such as acrylates and styrene. Further possible polyanions are perfluorinated colloid-forming polyanions, which are commercially available, for example, under the name The molecular weight of the polymer functionalized with acid groups and supplying polyanions is preferably 1,000 to 2,000,000, particularly preferably 2,000 to 500,000. Polymers functionalized with acid groups or their alkali metal salts are commercially available, such as polystyrene sulfonic acid and polyacrylic acid; or can be prepared by known methods (see, for example, Houben Weyl, Methoden der organischen Chemie, Vol. E 20, Macromolecular Substances (Makromolekulare Stoffe), Part 2, (1987), p. 1141, etc.). Particularly preferred polyanions are anions of polystyrene sulfonic acid.

[0086] The particles i) comprise a complex of polythiophene and a polyanion, particularly preferably a PEDOT / PSS complex. Such a complex can be obtained by oxidative polymerization of thiophene monomers, preferably 3,4-ethylenedioxythiophene, in the presence of a polyanion, preferably in aqueous solution, preferably by oxidative polymerization of 3,4-ethylenedioxythiophene in the presence of anions of polystyrenesulfonic acid.

[0087] The weight average diameter (d 50 ) is generally in the range of 10 nm to 2,000 nm, more preferably in the range of 20 nm to 500 nm, and more preferably in the range of 25 nm to 50 nm. The diameter distribution d 50 The value states that 50% of the total weight of all particles i) can be distributed to particles with a diameter less than or equal to d 50 The value of the particle (so d 50 The value represents the weight average particle size). As in the case where the PEDOT / PSS particles are dispersed in an aqueous solution, the particles are usually present in the form of swollen gel particles, and the particle size mentioned above refers to the particle size of the swollen gel particles and is determined by means of ultracentrifuge measurement.

[0088] According to a preferred embodiment of the liquid composition according to the present invention, the liquid composition comprises the complex i) of polythiophene and polyanion, preferably PEDOT / PSS complex, in an amount of 0.001 to 2.5 wt%, more preferably 0.005 to 1.0 wt% and most preferably 0.01 to 0.5 wt%, in each case based on the total weight of the liquid composition.

[0089] The liquid composition according to the invention comprises as component ii) a liquid phase, wherein the liquid phase comprises water iia) and at least one organic solvent iib) having a boiling point in the range of 110 to 250° C., preferably in the range of 120 to 225° C. and most preferably in the range of 130 to 200° C., measured at a pressure of 1013 mbar, and having a solubility in water of at least 10 wt.-%, preferably at least 25 wt.-%, more preferably at least 50 wt.-% and most preferably at least 90 wt.-%, measured at 25° C., wherein the liquid phase is an azeotrope or is capable of forming an azeotrope.

[0090] In addition, according to the present invention, preferably, the organic solvent iib) is an alcohol, an ether, preferably diethylene glycol dimethyl ether or a mixture thereof, more preferably an alcohol selected from the group consisting of ethylene glycol monoethyl ether (i.e., 2-ethoxyethanol), ethylene glycol monobutyl ether (i.e., 2-butoxyethanol), diacetone alcohol (i.e., 4-hydroxy-4-methylpentan-2-one) or a mixture of said alcohols, and most preferably diacetone alcohol.

[0091] According to a preferred embodiment of the liquid composition of the present invention, the liquid composition further comprises

[0092] iii) at least one additive selected from the group consisting of UV stabilizers, surface active substances, low boiling point solvents, pH adjusters, crosslinkers, rheology modifiers or a combination of at least two of said additives.

[0093] The UV stabilizer which may be present as at least one further additive iii) is preferably gallic acid, a derivative of gallic acid or a mixture thereof. Particularly preferred derivatives of gallic acid are esters of gallic acid with sugars, which are generally known as tannins or gallotannins (see Lump Chem ( Chemie), 10th edition (1999), page 4391). More preferred derivatives of gallic acid are alkyl, alkenyl, cycloalkyl, cycloalkenyl and aryl esters of gallic acid, preferably esters having 1 to 15 C atoms, preferably 1 to 6 C atoms in the alkyl, alkenyl, cycloalkyl, cycloalkenyl or aryl radical of the ester. Most preferred derivatives of gallic acid are gallotannins, such as tannic acid, or alkyl esters of gallic acid, such as methyl gallate, ethyl gallate, propyl gallate or mixtures of at least two of these esters.

[0094] According to a preferred embodiment of the liquid composition according to the present invention, the liquid composition comprises gallic acid, a derivative of gallic acid or a mixture thereof, preferably gallotannin, more preferably tannic acid, in an amount of 0.0001 to 5 wt%, more preferably 0.001 to 2.5 wt% and most preferably 0.01 to 1 wt%, in each case based on the total weight of the liquid composition. If the liquid composition comprises a mixture of gallic acid and its derivatives or a mixture of at least two derivatives of gallic acid as component iii), the above amounts represent the total amount of these components.

[0095] The crosslinking agent which may be present as at least one further additive iii) is preferably a tetraalkyl orthosilicate. Preferred tetraalkyl orthosilicates are selected from the group consisting of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, at least partially hydrolyzed products of these orthosilicates and mixtures of at least two of these orthosilicates, with the use of tetraethyl orthosilicate (TEOS) being particularly preferred.

[0096] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition comprises a tetraalkyl orthosilicate, preferably TEOS, in an amount of 0.01 to 15 wt %, more preferably 0.1 to 10 wt % and most preferably 1 to 5 wt %, in each case based on the total weight of the liquid composition. If the liquid composition comprises a mixture of two or more tetraalkoxysilanes as component iii), the above amounts represent the total amount of these components.

[0097] In the sense of the present invention, a "low-boiling solvent" which may be present as at least one further additive iii) is a solvent having a boiling point of less than 100° C., preferably less than 90° C. and more preferably less than 80° C., measured at a pressure of 1013 mbar. A preferred low-boiling solvent is ethanol. In this case, the liquid composition also preferably comprises a low-boiling solvent, preferably ethanol, in an amount of 10 to 90 wt.-%, more preferably 20 to 85 wt.-% and most preferably 30 to 80 wt.-%, in each case based on the total weight of the liquid composition.

[0098] In this context, it is also preferred that the volume ratio of water:ethanol in the liquid composition according to the invention is in the range of 1:1 to 1:25, preferably in the range of 1:2 to 1:20 and more preferably in the range of 1:3 to 1:10. The volumes are determined for the individual components before mixing.

[0099] Suitable surface-active substances which can be used as at least one further additive iii) are, for example, anionic surfactants, such as alkylbenzenesulfonic acids and salts, paraffinsulfonates, alcoholsulfonates, ethersulfonates, sulfosuccinates, phosphates, alkylethercarboxylates or carboxylates; cationic surfactants, such as quaternary alkylammonium salts; nonionic surfactants, such as linear alcohol ethoxylates, oxyalcohol ethoxylates, alkylphenol ethoxylates or alkyl polyglucosides, in particular those sold under the trademark and Commercially available surfactants.

[0100] The viscosity of the liquid composition according to the invention is preferably between 10 and 100 mPa×s (measured by rheometer at 20° C. and at 100 s -1 More preferably, the viscosity is between 1 and 10 mPa×s, particularly preferably between 2 and 5 mPa×s. Adjustment of the viscosity can be achieved, for example, by adding suitable rheology modifiers as further additives iii).

[0101] According to a preferred embodiment of the liquid composition of the present invention, the pH value of the liquid composition is not less than 2.5, more preferably the pH value is in the range of 2.5 to 6, even more preferably in the range of 2.5 to 5 and most preferably in the range of 2.5 to 4, wherein the pH value is measured at a temperature of 25°C. The pH value can be adjusted by adding a suitable pH regulator such as an organic acid or an inorganic acid as a further additive iii) to the liquid composition. Suitable acids are inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, silicic acid or a mixture of at least two of these inorganic acids; or organic acids such as acetic acid, formic acid, benzoic acid, p-toluenesulfonic acid, PSS or a mixture of at least two of these organic acids; or a mixture of at least one of these inorganic acids and at least one of these organic acids.

[0102] The liquid composition according to the present invention may further comprise

[0103] iv) at least one other polymer different from polythiophene and polyanion,

[0104] Wherein the at least one other polymer iv) preferably acts as an adhesive. Suitable adhesives are selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylate, polyacrylamide, polymethacrylate, polymethacrylamide, polyacrylonitrile, styrene / acrylate, vinyl acetate / acrylate, ethylene / vinyl acetate copolymer, polybutadiene, polyisoprene, polystyrene, polyether, polyester, sulfonated polyester, polycarbonate, polyurethane, polyamide, polyimide, polysulfone, melamine-formaldehyde resin, epoxy resin, silicone resin, silane resin, cellulose or a mixture of at least two of these adhesives. Other useful polymer adhesives are preferably also adhesives obtained by adding a crosslinking agent, such as a melamine compound, a blocked isocyanate or a functionalized silane (e.g. 3-glycidyloxypropyltrialkoxysilane, tetraethyl orthosilicate and tetraethyl orthosilicate hydrolyzate) to a crosslinkable polymer, such as polyurethane, polyacrylate or polyolefin, and then crosslinking. Water soluble binders such as sulfonated polyesters are particularly preferred.

[0105] According to a preferred embodiment of the liquid composition according to the present invention, the liquid composition comprises water (iia) in an amount in the range of 10 to 98 wt-%, preferably in the range of 20 to 97 wt-%, more preferably in the range of 30 to 96 wt-% and even more preferably in the range of 40 to 95 wt-%, in each case based on the total weight of the liquid composition.

[0106] According to another preferred embodiment of the liquid composition according to the present invention, the liquid composition comprises at least one organic solvent iib) in an amount of less than 10 wt%, preferably less than 8.5 wt% and more preferably less than 7 wt%, preferably ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diacetone alcohol or a mixture thereof, more preferably diacetone alcohol, in each case based on the total weight of the liquid composition. In the case of two or more organic solvents iib), the amount defines the total amount of organic solvents iib).

[0107] The dried layer prepared with the liquid composition according to the invention preferably has a 6 Ω / sq, preferably at least 5×10 6 Ω / sq and more preferably at least 1×10 7 Sheet resistance of Ω / sq.

[0108] The dry layer produced with the liquid composition according to the invention preferably has an internal transmission of at least 98%, preferably at least 98.5%, more preferably at least 99% and most preferably at least 99.5%.

[0109] The dried layer produced with the liquid composition according to the invention preferably has a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H and most preferably at least 9H.

[0110] The above object is also achieved by a method for producing a layered body, comprising the following method steps:

[0111] A) providing a substrate;

[0112] B) applying a liquid composition according to the invention to this substrate;

[0113] C) at least partially removing said liquid phase ii) from said liquid composition to obtain a layered body comprising a conductive layer applied onto said substrate.

[0114] In method step A), a substrate is first provided, wherein the nature of the substrate depends on the intended purpose for which the composition according to the invention is to be employed. Suitable substrates include films, particularly preferably polymer films, very particularly preferably polymer films formed from thermoplastic polymers, or glass plates.

[0115] Next, in method step B), the liquid composition according to the invention is applied to the substrate by known methods, for example by spin coating, dipping, pouring, dripping, spraying, atomizing, knife coating, slot coating, brushing or printing, for example by inkjet printing, screen printing, gravure printing, offset printing or pad printing, preferably by slot coating, spraying or inkjet printing to a wet film thickness of, for example, 0.5 μm to 250 μm, preferably to a wet film thickness of 2 μm to 50 μm.

[0116] Next, in method step C), at least a portion of the liquid phase ii) is removed from the liquid composition to obtain a layered body comprising the conductive layer applied to the substrate, this removal preferably being carried out by drying the substrate coated with the composition at a temperature in the range of 20°C to 200°C.

[0117] The above mentioned objects are also achieved by using a layered body obtainable by the method described above. In this case, it is particularly preferred that the conductive layer of the layered body is characterized by at least one of the following properties (α1) to (α3), preferably all of these properties:

[0118] (α1) Sheet resistance is at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq and more preferably at least 1×10 7 Ω / sq;

[0119] (α2) an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%;

[0120] (α3) The pencil hardness is at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.

[0121] The above mentioned objects are also contributed to by using a liquid composition according to the invention or a liquid composition obtainable by the method according to the invention for producing a layered body comprising a substrate and a conductive layer applied onto the substrate.

[0122] The layered bodies which can be prepared with the liquid composition according to the invention are particularly suitable for use as electronic components, in particular as conductive or antistatic components, as transparent heating elements or as electrodes. They can advantageously be transparent.

[0123] These laminae can be used as electronic components, for example also in films, packaging of electronic components, for modifying plastic films and for coating screens. They can further be used, for example, as transparent electrodes in displays, for example as a substitute for indium tin oxide electrodes, or as electrical conductors in polymeric electronic devices. Other possible uses are sensors, batteries, solar cells, electrochromic windows (smart windows) and displays and corrosion protection.

[0124] In view of the low conductivity, high UV stability and high scratch resistance of the coatings obtained with the liquid compositions according to the invention, these liquid compositions are particularly suitable for producing antistatic coatings or electromagnetic radiation shielding. In addition, they are particularly suitable for preparing hole transport layers in organic light-emitting diodes (OLEDs) or in organic photovoltaic (OPV) elements or in organic photodetectors (OPDs).

[0125] The invention will now be explained in more detail with the aid of non-limiting examples.

[0126] Test Method

[0127] Determination of sheet resistance

[0128] The sheet resistance is measured using a Hiresta-UX high resistivity meter (model MCP-HT 800) equipped with a ring probe URS RMH 214. The measurement is performed at 100V.

[0129] Pencil hardness

[0130] The pencil hardness of the coatings was determined by sliding various pencils of different hardness across the coating deposited on a glass plate according to ISO 15184. The possible influence of the pencil marks on the coating was assessed by visual inspection.

[0131] Transmittance

[0132] The internal transmittance of the coated substrate is measured on a 2-channel spectrometer (Lambda900, PerkinElmer). To exclude the interference of scattered light here, the sample is measured in a photometer ball (Ulbricht sphere), whereby its scattered light and transmitted light are detected by a photodetector. Therefore, the transmittance is understood to mean the absorptivity of the coating and the substrate. First, the transmittance of a pure substrate is measured. A Melinex 506 film with a thickness of 175 μm is used as a substrate. Thereafter, the coated substrate is measured. The transmission spectrum is recorded in the visible light range, i.e. from 320 nm to 780 nm at a step size of 5 nm.

[0133] Taking 10° observation angle and light type D65 as the basis, the standard color value Y of the sample is calculated from the spectrum according to DIN 5033. The internal transmittance is calculated from the ratio of the standard color value (Y) of the substrate with coating to the standard color value (Y0) of the substrate without coating. The internal transmittance corresponds to Y / Y0×100%. For simplicity, it is only referred to as transmittance in the following text.

[0134] Examples

[0135] Example 1

[0136] Clevios P ​​VP CH 8000 (Heraeus) (PEDOT / PSS—weight ratio 1:20; solid content: 2.8 wt %) was mixed with different amounts of different solvents (all completely soluble in water) as indicated in Table 1. For example, to obtain sample 2, 95 g Clevios P ​​VP CH 8000 was mixed with 5 g ethylene glycol monobutyl ether and stirred for 10 minutes. The dispersion was tested for clogging of the nozzle. The samples were spin-coated onto a glass substrate and dried at 200° C. for 15 minutes. The sheet resistance was determined. Table 1 summarizes the results. Inventive samples 2, 3, 4, 5 and 6 were compared with reference samples 7 and 8.

[0137]

[0138] Table 1

[0139] Only high boiling point solvents that form azeotropes with water do not significantly change the resistivity of the CH 8000 film, whereas DMSO or ethylene glycol do.

[0140] Example 2

[0141] 0.1 g of tannic acid was dissolved in 84 g of ethanol. 12.6 g of Clevios P ​​(Heraeus) was placed in a 250 ml glass beaker. Under stirring, the solution of tannic acid in ethanol was added to the Clevios P ​​dispersion. 3.1 g of tetraethyl orthosilicate was added to the mixture. The pH was adjusted to 3.3. Different amounts of additional solvent (as indicated in Table 2) were added to the dispersion. The mixture was stirred at room temperature for 30 minutes.

[0142] Films having a wet film thickness of 12 μm were deposited on alkali-free glass using a wire bar and then dried at 120° C. for 20 minutes. Table 2 shows the results. Inventive samples 10 and 11 were compared with reference samples 9 and 12 to 16.

[0143]

[0144]

[0145] Table 2

[0146] Example 3

[0147] Clevios P ​​VP CH 8000 was concentrated to 3.24% solids. To this "concentrated Clevios CH 8000" were added different amounts of various high boiling point solvents (PEDOT / PSS—weight ratio 1:20; solid content: 3.24 wt%). The samples were spin coated onto glass substrates and dried at 200°C for 15 minutes. The sheet resistance was determined as shown in Table 3. The layer thickness of the samples was 200 nm.

[0148]

[0149] Table 3

[0150] Inventive samples 18 to 24 were compared with reference sample 17.

Claims

1. A liquid composition comprising: i) particles comprising a complex of a polythiophene and a polyanion, wherein the polythiophene is poly(3,4-ethylenedioxythiophene) and wherein the polyanion is an anion of polystyrene sulfonic acid; wherein the liquid composition comprises the complex of the polythiophene and the polyanion in an amount ranging from 0.001 to 2.5 wt % based on the total weight of the liquid composition; ii) a liquid phase, wherein the liquid phase comprises iia) water, wherein the liquid composition comprises water in an amount ranging from 10 to 98 wt % based on the total weight of the liquid composition; and iib) at least one organic solvent having - a boiling point in the range of 110 to 250° C., measured at a pressure of 1013 mbar, and - a solubility in water of at least 10 wt % measured at 25°C; wherein the organic solvent iib) is an alcohol, an ether or a mixture thereof; wherein the liquid composition comprises the at least one organic solvent in an amount of less than 10 wt % based on the total weight of the liquid composition; wherein the liquid phase is an azeotrope or is capable of forming an azeotrope; wherein the liquid composition further comprises a low boiling point solvent as at least one other additive iii), wherein the low boiling point solvent is ethanol; The dry layer prepared by using the liquid composition has a thickness of at least 5×10 6 Sheet resistance of Ω / sq.

2. The liquid composition according to claim 1, wherein the alcohol is selected from the group consisting of ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diacetone alcohol, diethylene glycol dimethyl ether or a mixture thereof.

3. The liquid composition according to claim 1 or 2, wherein the liquid composition further comprises a crosslinking agent as at least one other additive iii), wherein the crosslinking agent is tetraethyl orthosilicate (TEOS).

4. A method for preparing a layered body, comprising the following method steps: A) providing a substrate; B) applying the liquid composition according to any one of claims 1 to 3 to the substrate; C) at least partially removing the liquid phase ii) from the liquid composition to obtain a layered body comprising a conductive layer applied onto the substrate, The application of the liquid composition in method step B) is carried out by spraying or inkjet printing.

5. Use of the liquid composition according to any one of claims 1 to 3 for forming an antistatic coating or an electromagnetic radiation shield or for preparing a hole transport layer in an organic light emitting diode (OLED) or an organic photovoltaic (OPV) element or an organic photodetector (OPD).

Citation Information

Patent Citations

  • Polythiophenes, process for their preparation and their use

    EP0339340A2

  • New polythiophene dispersions, their preparation and their use

    EP0440957A2

  • Conductive coatings

    EP0686662A2

  • Solvents for pedot-solutions for ink-jet printing

    CN101228645A

  • Conductive composition, composite material and production method therefor

    CN104245831A